PENGEMBANGAN MEDIA SMART BOX UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI BILANGAN CACAH KELAS III SDN KETETANG 1 - Haya Zahra; Mohammad Edy Nurtamam; Ahmad Sudi Pratikno; Ana Naimatul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop smart box media and determine the validity and attractiveness of smart box media to improve problem-solving skills in the material of whole numbers of grade III SDN Ketetang I. The type of research used is research and development (Research and Development) using a 4-D model that includes the stages of define, design, develop, and disseminate. Research data were obtained from teacher interviews, student needs questionnaires, teacher response questionnaires, student response questionnaires, teacher activity observation sheets, student activity observation sheets, media expert validation, material expert validation, and learning design expert validation. The validation results by material experts obtained a percentage of 84%, media experts 90%, and learning design experts 99% with a very valid category. The attractiveness of smart box media is seen from the results of teacher response questionnaires and student responses. The results of student response questionnaires obtained a percentage of 98% while the results of teacher response questionnaires obtained a percentage of 94%. Based on these results, it can be concluded that smart box media learning media is included in the very interesting category. The test subjects in this study were 31 students of grade III of SDN Ketetang 1.